2010
DOI: 10.1007/s11064-010-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Depression of Energy Metabolism after Microdialysis Probe Implantation is Distinct from Ischemia-Induced Changes in Mouse Brain

Abstract: The current study used measurements of metabolites and markers of membrane integrity to determine the most suitable time point for microdialysis experiments following probe implantation. Leakage of Evans blue and sodium fluorescein indicated increased BBB permeability only immediately (15 min), but not 1.5 and 24 h following probe implantation. Acute implantation decreased glucose and lactate levels relative to the levels after 24 h (to 13-37% and 25-60%, respectively). No change in extracellular levels of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…We expected post-TAI hypoxia to aggravate the metabolic disarray caused by diffuse axonal injury and employed the microdialysis technique to monitor changes of various metabolites over 4 days. Due to the detection of significant alterations in brain metabolites following the implantation of microdialysis probe in uninjured sham animals as reported by others [63], we chose to discard samples over the first 20 h following probe implantation to reduce the artifact from the needle injury. In this study we were only present data of glucose, lactate and glutamate from the microdialysates, since pyruvate is known to become unstable after prolonged storage time (CMA Microdialysis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected post-TAI hypoxia to aggravate the metabolic disarray caused by diffuse axonal injury and employed the microdialysis technique to monitor changes of various metabolites over 4 days. Due to the detection of significant alterations in brain metabolites following the implantation of microdialysis probe in uninjured sham animals as reported by others [63], we chose to discard samples over the first 20 h following probe implantation to reduce the artifact from the needle injury. In this study we were only present data of glucose, lactate and glutamate from the microdialysates, since pyruvate is known to become unstable after prolonged storage time (CMA Microdialysis).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore allowed the rats to recover for 4 hours after TAI before implanting the microdialysis probe. In accordance with others [63], our study has shown that in sham rats energy metabolism is altered during the first 24 h following microdialysis probe implantation, therefore we chose to examine only the data from 20 h onwards to reduce the "probe effect".…”
Section: Discussionmentioning
confidence: 99%
“…Both oxygen-derived free radicals and reactive nitrogen species are involved in activating several pathways involved in cell death following stroke, such as apoptosis and inflammation [37-39]. A reduction of oxygen supply also leads to the accumulation of lactate via anaerobic glycolysis and so to acidosis [40-43]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the absence of any distinguishable difference in implanted hippocampal tissue visualized under cresyl violet-photomicrograph across concussion and sham groups as well as the stability of ECF GABA levels throughout all dialysate sampling times suggest that only slight, if any, additional damage to hippocampal tissue could be attributed to leaving the microdialysis probe inserted during impact 27 . Alternatively, having kept the probe inserted throughout the entire experimental procedure significantly reduced the likelihood of inducing repeated damage associated with microdialysis probe insertion, including damage to the mTBI-sensitive blood-brain barrier 28 . Interestingly, a one-time probe insertion into healthy brain tissue has been shown to leave the blood-brain barrier intact 28 .…”
Section: Extracellular Glutamate Measured By Microdialysis and Methodmentioning
confidence: 99%
“…Alternatively, having kept the probe inserted throughout the entire experimental procedure significantly reduced the likelihood of inducing repeated damage associated with microdialysis probe insertion, including damage to the mTBI-sensitive blood-brain barrier 28 . Interestingly, a one-time probe insertion into healthy brain tissue has been shown to leave the blood-brain barrier intact 28 . Perhaps most importantly, uninterrupted dialysate collection throughout the entire experimental procedure allowed us to include a gold standard tissue recovery and equilibration period before beginning sample collection 29 .…”
Section: Extracellular Glutamate Measured By Microdialysis and Methodmentioning
confidence: 99%